Comparative assessment of cognitive function of asthmatic and non-asthmatic children in Ilorin, Nigeria - Mohammed, Salihu Sheni; Ibraheem, Rasheedat Mobolaji; Abdulkadir, Mohammed Baba; Adeboye, Muhammed Akanbi Nurudeen; Gobir, Aishatu Ahmed; Johnson, Wahab Babatunde Rotimi (Indonesian Pediatric Society, 2024)
Background The presence of asthma in children may negatively impact their cognitive function, possibly due to intermittent hypoxia from repeated acute exacerbations, sleep deprivation, and school absenteeism. However, conflicting reports abound on cognitive performance among children with asthma. Objective To assess and compare the cognitive function of asthmatic and non-asthmatic children in Ilorin, Nigeria. Methods This cross-sectional study compared the cognitive performance scores of 66 children with asthma aged 6-17 years, and the corresponding scores of 66 healthy age- and gender-matched children without asthma. Data obtained included sociodemographic, anthropometric, and clinical details. Cognitive function was assessed with the Raven's Progressive Matrices (RPM) psychometric test. Results The male: female ratio was 1.3:1. The median RPM score of 50.0 [interquartile range (IQR) 25.0-75.0] in children with asthma was significantly higher than that of non-asthmatic children [32.5 (IQR 10.0-50.0)]; (P=0.016). A significantly higher proportion of asthmatic subjects (74.2%) were in the high grade RPM score category compared to the non-asthmatic children’s concomitant proportion (57.6%). Asthmatic subjects were twice as likely to belong to the high grade RPM score category than their non-asthmatic counterparts (OR=2.12; 95%CI 1.02 to 4.44; P=0.043). There was no significant association between RPM score grade and clinical severity of asthma in the subject population (P=0.554). Conclusion Children with asthma perform better in cognitive function assessment, using RPM test, compared to their non-asthmatic counterparts in Ilorin, Nigeria.